Engineering Saccharomyces cerevisiae for medical applications - Carla Maneira; Alexandre Chamas; Gerald Lackner (Microbial Cell Factories)
Abstract Background During the last decades, the advancements in synthetic biology opened the doors for a profusion of cost-effective, fast, and ecologically friendly medical applications priorly unimaginable. Following the trend, the genetic engineering of the baker’s yeast, Saccharomyces cerevisiae, propelled its status from an instrumental ally in the food industry to a therapy and prophylaxis aid. Main text In this review, we scrutinize the main applications of engineered S. cerevisiae in the medical field focusing on its use as a cell factory for pharmaceuticals and vaccines, a biosensor for diagnostic and biomimetic assays, and as a live biotherapeutic product for the smart in situ treatment of intestinal ailments. An extensive view of these fields' academic and commercial developments as well as main hindrances is presented. Conclusion Although the field still faces challenges, the development of yeast-based medical applications is often considered a success story. The rapid advances in synthetic biology strongly support the case for a future where engineered yeasts play an important role in medicine.